2014
DOI: 10.1007/s00280-014-2657-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of potential drug–drug interaction in hematopoietic stem cell transplantation

Abstract: Patients undergoing hematopoietic stem cell transplantation (HSCT) are at risk of developing potential drug-drug interactions (PDDIs). The aim of this study was to assess the prevalence of PDDIs that occur in HSCT patients on the day of hematopoietic stem cell infusion. We performed a cross-sectional study based on the evaluation of prescriptions to HSCT patients on the day of infusion (day 0). The PDDIs were analyzed using the DRUG-REAX(®) system and classified according to the severity level, available scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
1
20
1
1
Order By: Relevance
“…In agreement with a study that shows the complexity of drug therapy in HSCT (20) , the activity related to medication was scored by the entire sample. In these patients, drugs are administered almost exclusively intravenously (IV) and, in a IV line replacement a nurse may spend, on average, 11.95 minutes (21) .…”
Section: Discussionsupporting
confidence: 68%
“…In agreement with a study that shows the complexity of drug therapy in HSCT (20) , the activity related to medication was scored by the entire sample. In these patients, drugs are administered almost exclusively intravenously (IV) and, in a IV line replacement a nurse may spend, on average, 11.95 minutes (21) .…”
Section: Discussionsupporting
confidence: 68%
“…Multiple drug therapy is common in today’s oncology medical practice, increasing the risk of single and/or multiplex drug-drug interactions (DDIs) – that often lead to adverse drug toxicities and unanticipated treatment outcomes [13]. HSCT patients are commonly subjected to poly-pharmacy, taking on average at least 8 or more drugs on admission, and they are exposed for lengthy periods of time to complex drug regimens consisting of multiple pharmacological classes, many of which interact with each other [1315].…”
Section: Introductionmentioning
confidence: 99%
“…HSCT patients are commonly subjected to poly-pharmacy, taking on average at least 8 or more drugs on admission, and they are exposed for lengthy periods of time to complex drug regimens consisting of multiple pharmacological classes, many of which interact with each other [1315]. In HSCT patients, the signs/symptoms of a DDI may go undetected in the pre-HSCT phase and/or be dismissed as a symptom of the primary tumor, but may appear during later periods following the transplant [15].…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy is a factor which is well documented in the literature as a factor associated with PDDI, independent of the disease investigated, country or place of care, and health treatment [8,9,[12][13][14][15][16][17][18]. The polypharmacy recorded in this study is expected for this population, given that these individuals present an increased risk for cardiovascular diseases, such as SAH, dyslipidemias, and abnormalities related to coagulation.…”
Section: Discussionmentioning
confidence: 93%
“…Studies in different scenarios have indicated negative outcomes related to DDI, which can result in adverse events, a reduction or increase in the medications' therapeutic effects, an increase in the toxicity of medications, an increase in the health services' costs, failure of the treatment, and/or serious complications for the patient, including the risk of death [8,9,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%